Indigenous Foods: Resilience against Emerging Diseases - Tandon, Achla Pritam; Ghorai, Soma Mondal (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The harmful effects of processed food have seen a worldwide increase in the number of people falling prey to lifestyle-related diseases. The latest in the row of diseases striking humans has been the deadly COVID-19, which also we would like to critique as a consequence of reduced immunities besides compromised health and sanitation restrictions being exercised. Ironically, Indigenous people, despite their greater challenges with the natural elements, lower levels of infrastructural and medicinal access, we're able to garner their coping mechanisms to curb death counts in their communities. It was observed that support groups at the village level emerged along with traditional food choices as well as them choosing holistic ways of healing. This paper is an attempt to the forefront the idea of ‘going back to basics along with our modern-day lifestyles, dietary preferences, and food consumption patterns.